Dynamic Characteristics, Analysis, and Measurement of a Large Optical Mirror Processing System - Zujin Jin; Zixin Yin; Hao Liu; Fuchao Liu (Machines)
Optical mirrors have high requirements for surface precision, requiring ultra-precision processing. The revolving movement of a computer-controlled optical surfacing (CCOS) grinding system will induce vibrations in a five-degrees-of-freedom hybrid processing robot (5-DOF-HPR) and a flexible support system (FSS) in a large optical mirror processing system (LOMPS). As a result, the mirror surface will vibrate, which will ultimately affect the surface accuracy of the final optical mirror. Therefore, the differential equation representing the vibration of the 5-DOF-HPR is established based on the spatial beam unit, which transforms the generalized coordinates into modal coordinates, thereby removing the coupling terms of the vibration differential under generalized coordinates. At the same time, a dynamic analysis of the CCOS grinding system is performed, and the magnitude and direction of the centrifugal force and reaction force are calculated. Then, the natural frequencies of the 5-DOF-HPR and the FSS are measured experimentally and compared with the simulation results; thus, the accuracy and effectiveness of the model are verified. Finally, the vibration characteristics of the processed optical mirrors under different influencing factors are obtained. A theoretical and experimental basis for parameter optimization and path planning of the LOMPS is provided to improve the surface accuracy of the processed optical mirror.